Investor's Business Daily and the making of millionaires : how IBD rewrote the rules of investing and business news - Saito-Chung, David (McGraw-Hill, 2005)
"In November 1983, William O'Neil laid out his plans to start a brand-new national paper, Investor's Daily (its original name until Sept. 16, 1991). Unlike the Wall Street Journal, the industry's heavyweight champ for the past century, IBD would give daily ratings for every stock to measure profit growth and stock-price strength. For the first time, investors would be able to compare stocks against other stocks. The paper would also print charts of the major indexes so readers could study the market's overall price trend. It would run about 100 small weekly charts daily to ensure that no great stock would be ignored. IBD would feature new growing companies in detail and update a table of nearly 200 industry groups ranked by six-month performance. In short, IBD wouldn't be like any other financial publication." "By providing a daily education on sound stock investing based on 50 years of fact-based stock market research, IBD has become a unique tool and information source that helps investors build wealth through buying, holding, and eventually selling the best growth stocks in the market. Along the way, the paper has debunked many of the myths on investing by highlighting the most relevant data for finding the big winners. This is O'Neil's legacy - a wealth of insight that will change the way you invest and succeed."--BOOK JACKET.